Giant Lipoma of The Breast: Special Clinical Finding - Muhammad Zaki Abdul Hafiz; Daan Khambri; Anandia Putriyuni (Biomedical Journal of Indonesia, 2021)
Lipomas are the most common benign tumors of mesenchymal origin. Lipoma of breast is somewhat difficult to diagnose clinically because of fatty consistency of breast. Giant lipoma is the mass of lipoma that exceeds at least 10 cm in one dimension or weighs a minimum of 1000 gr.Only very few case reports giant lipoma of the breast available in literature because rarity in size and location. Due to the fatty composition of the breast, difficulties in diagnosis, threatment, and reconstruction are often encountered.Presently, we have reported a case of this rare entity in 49 years old female with giant tumor of the left breast that most of its mass, causing breast asymmetry and feel heavy. The operative finding: looks like lipoma between pectoralis major muscle and pectoralis minor muscle with a diameter of 31 cm and weighs 3.1 kg. After excision the tumor we need to mammoplasty.Pathology anatomy examination showed a lipoma.